Instruments for the assessment of quality of life in children and adolescents with Down syndrome: a scoping review - Eliana-Isabel Rod; Mayra Liseth Díaz Galvis; Paula Catalina Medina Prieto; Olga-Cecilia; Martha-Rocío; Nelcy Rodríguez Malagón (BMC, 2024)
Abstract The construct of quality of life (QoL) includes aspects of health and well-being of people. Down syndrome [DS] or trisomy 21 is one of the most common congenital anomalies. DS is characterized by motor and cognitive alterations that affect health and QOL of both the child and caregiver. In pediatrics, there are various instruments to assess Health-Related Quality of Life (HRQoL) and QoL. The advantage of these instruments is that they can be implemented in any type of disease and population in general. However, they may have certain disadvantages, such as the difficulty in evaluating specific aspects of each disease or condition related to Down syndrome. The aim of this study was to identify 1: instruments used to assess quality of life in children with Down syndrome. 2: psychometrics properties of instruments validated in children with Down syndrome to assess quality of life. Methods A Scoping review was conducted to identify instruments used in children and adolescents with Down syndrome, and a second systematic searched psychometric properties of these instruments. The electronic databases PubMed, Embase, Epistemonikos and other sources were explored with a search strategy that included keywords such as "Down syndrome," "Quality of life" or "Life Quality," "Health-Related Quality of Life" and psychometrics properties. The quality of the included studies was evaluated using the COSMIN (Based Standards for the Selection of Health Measurement Instruments) methodology. Results Twenty-seven studies were selected that used twelve instruments to evaluate quality of life in children or adolescents with Down syndrome. Two of the twelve evaluated quality of life and ten health-related quality of life. In the second search, ten studies reported the psychometric properties of six instruments evaluated in minors with Down Syndrome. Conclusion There is limited information available regarding the psychometric properties of instruments used to assess quality of life, particularly health-related quality of life. Commonly employed instruments in this area include the PedsQL 4.0 and KIDSCREEN. Notably, while the PedsQL 4.0 lacks specific evaluation in children with DS, data from KIDSCREEN assessments are inconsistently reported. Rigorous evaluation of the performance of Kidslife and Kidslife Down in clinical settings is necessary, or the development of new instruments tailored for children with DS is warranted to comprehensively assess quality of life in clinical settings.